Evolution of the analytical scattering model of live Escherichia coli. Issue 2 (3rd March 2021) - Semeraro, Enrico F.; Marx, Lisa; Mandl, Johannes; Frewein, Moritz P. K.; Scott, Haden L.; Prévost, Sylvain; Bergler, Helmut; Lohner, Karl; Pabst, Georg
Abstract : Structural and compositional information about Escherichia coli cells is summarized and translated into an analytical multi‐length‐scale scattering form factor model of live bacterial suspensions. Abstract : A previously reported multi‐scale model for (ultra‐)small‐angle X‐ray (USAXS/SAXS) and (very) small‐angle neutron scattering (VSANS/SANS) of live Escherichia coli was revised on the basis of compositional/metabolomic and ultrastructural constraints. The cellular body is modeled, as previously described, by an ellipsoid with multiple shells. However, scattering originating from flagella was replaced by a term accounting for the oligosaccharide cores of the lipopolysaccharide leaflet of the outer membrane including its cross‐term with the cellular body. This was mainly motivated by (U)SAXS experiments showing indistinguishable scattering for bacteria in the presence and absence of flagella or fimbrae. The revised model succeeded in fitting USAXS/SAXS and differently contrasted VSANS/SANS data of E. coli ATCC 25922 over four orders of magnitude in length scale. Specifically, this approach provides detailed insight into structural features of the cellular envelope, including the distance of the inner and outer membranes, as well as the scattering length densities of all bacterial compartments. The model was also successfully applied to E. coli K12, used for the authors' original modeling, as well as for two other E. coli strains. Significant differences were detected between the different strains in terms of bacterial size, intermembrane distance and its positional fluctuations. These findings corroborate the general applicability of the approach outlined here to quantitatively study the effect of bactericidal compounds on ultrastructural features of Gram‐negative bacteria without the need to resort to any invasive staining or labeling agents.